The Effect Of Applying Guided Discovery Learning (GDL) Model on the Students' Critical Thinking Abilities In Budidaya Lele (BDL) Subject Grade 11 SMA N 10 Semarang - Amalia, Devi; Yuniastuti, Ari; Isnaeni, Wiwi (FMIPA UNNES, 2019)
SMA Negeri 10 Semarang is a school in Semarang which applies Budidaya Lele (BDL) subject. This subject is in accordance with the learning reference in the 2013 Curriculum. One of the goals to be achieved in the 2013 Curriculum is improving students’ critical thinking abilities. However, the facts show that students’ critical thinking abilities in SMA Negeri 10 Semarang are still low. One factor causing the low level of critical thinking abilities is conventional learning model implementation and teacher-centered. One of the learning models that can help improve students’ critical thinking abilities is Guided Discovery Learning (GDL). This study aims to investigate the effect of GDL model on students’ critical thinking abilities of grade 11 science in BDL subject. The sampling technique was purposive sampling. The research object was students in 11 science 4 class as the experimental class applying GDL model and students in 11 science 3 class as the control class applying conventional learning model. The aspects of critical thinking abilities measured were ability to provide simple explanation, ability to develop basic skills by using the indicators of considering trusted sources, ability to draw conclusion, ability to provide further explanation, and ability to manage strategies and tactics. The data was collected through tests and questionnaires. The data of test results was analyzed by using T test using SPSS and N-Gain test in Microsoft Excel 2010, while the questionnaire data was descriptively analyzed. The data analysis result of T test shows a mean difference in the experiment class and control class indicated by sig. value (2-tailed) as much as 0.000. The result of N-gain test, the experimental class has 0.43 value with medium criteria and the control class has 0.24 value with low criteria. The results of the two tests show that GDL model implementation affects students’ critical thinking abilities in the experimental class in BDL lesson. Students in the experimental class applying GDL model have better critical thinking abilities compared to students in the control class which does not apply GDL model.